70th Anniversary Collection for the Microbiology Society: Microbial Genomics. Issue 6 (14th December 2015) - Bentley, Stephen; Thomson, Nicholas
Abstract : In the context of the Microbiology Society's 70th anniversary celebration, Microbial Genomics ( MGen ) is the new baby of the Society's publishing family. Born on 15 July 2015, it is still in its infancy but already showing promising signs, and we have great hopes and expectations for the future. The journal captures a new and expanding area of research, one which is already having a major impact on research in microbiology, and has and continues to accelerate discoveries in the field.